Lentes de contato para correção estética - Martins, Jéssica Maria de Freitas Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The minimally invasive preparations for aesthetic smile correction have been applied as a means of treatment in cases of diastema closure, re-alignment and alignment of the teeth. Such preparations are limited to enamel, thus favoring adhesion with indirect restorations. The materials used for the lenses or microblades are vitreous ceramics, such as lithium disilicate, which have high tack to the dental substrate through adhesive cementation procedures. Therefore, the objective of this work was to describe the protocols for the development of minimally invasive prosthetic preparations, as well as the procedures of adhesive cementation of contact lenses for aesthetic correction of the smile involving the teeth 11, 12, 13, 14, 15, 21, (E.max press HT) and incisal laminate with nanofluorapatite ceramics (e.maxceram) were obtained by the use of the lithium disilicate (e-max) - Cut back technique. The conclusion of the case shows that it is possible to obtain excellent aesthetic and functional results, preserving the health of the periodontal tissues and offering satisfaction to the patient

Os preparos minimamente invasivos para correção estética do sorriso tem sido aplicados como meio de tratamento em casos de fechamento de diastemas, recontorno e alinhamento dos dentes. Tais preparos ficam limitados ao esmalte, favorecendo desta forma a adesividade com as restaurações indiretas. Os materiais utilizados para as lentes ou microlâminas são cerâmicas vítreas, como o dissilicato de lítio que possuem alta adesividade ao substrato dental através dos procedimentos de cimentação adesiva. Sendo assim, o objetivo deste trabalho foi descrever os protocolos de desenvolvimento de preparos protéticos minimamente invasivos, bem como os procedimentos de cimentação adesiva de lentes de contato para correção estética do sorriso envolvendo os dentes 11, 12, 13, 14, 15, 21, 22, 23, 24, 25. A cerâmica utilizada para o caso foi o dissilicato de lítio (e-max) obtido através da injeção de Ingots HT (e.max press HT) e estratificado incisal com cerâmica de nanofluorpatita (e.maxceram)- técnica cut back. A conclusão do caso mostra que é possível obter excelentes resultados estéticos e funcionais, preservando a saúde dos tecidos periodontais e oferecendo satisfação ao paciente
Keywords: Estética dentária; Cerâmicas odontológicas; Facetas dentárias; Esthetics, Dental